2005
DOI: 10.1167/iovs.04-1181
|View full text |Cite
|
Sign up to set email alerts
|

ATP Release through Connexin Hemichannels in Corneal Endothelial Cells

Abstract: Hemichannels contribute to ATP release on mechanical stimulation in BCECs. The released ATP contributes to propagation of the Ca(2+) wave.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
208
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(219 citation statements)
references
References 71 publications
10
208
1
Order By: Relevance
“…A Px1 mimetic peptide with apparent specific blocking effect was also recently reported ( 110 pxn1) (Pelegrin and Surprenant 2006). A large number of publications demonstrate specific effects of some of these peptides on connexin hemichannels by using in parallel scrambled peptide versions, additional hemichannel blockers and/or studies of their effects on connexin-specific expression systems (Braet et al 2003a(Braet et al , 2003bPearson et al 2005;Gomes et al 2005;Eltzschig et al 2006;Takeuchi et al 2006;DeVuyst et al 2006;De Vuyst et al 2007;Retamal et al 2006Retamal et al , 2007bShintani-Ishida et al 2007). However, it was recently reported that some Cx32, Cx43, and Px1 mimetic peptides cause non-specific blockade of hemichannels formed by Px1, Cx46, and a connexin Cx32 chimera carrying the first extracellular loop of Cx43 (Cx32E143) in the oocyte expression system (Wang et al 2007).…”
Section: Pharmacology Of Hemichannelsmentioning
confidence: 88%
“…A Px1 mimetic peptide with apparent specific blocking effect was also recently reported ( 110 pxn1) (Pelegrin and Surprenant 2006). A large number of publications demonstrate specific effects of some of these peptides on connexin hemichannels by using in parallel scrambled peptide versions, additional hemichannel blockers and/or studies of their effects on connexin-specific expression systems (Braet et al 2003a(Braet et al , 2003bPearson et al 2005;Gomes et al 2005;Eltzschig et al 2006;Takeuchi et al 2006;DeVuyst et al 2006;De Vuyst et al 2007;Retamal et al 2006Retamal et al , 2007bShintani-Ishida et al 2007). However, it was recently reported that some Cx32, Cx43, and Px1 mimetic peptides cause non-specific blockade of hemichannels formed by Px1, Cx46, and a connexin Cx32 chimera carrying the first extracellular loop of Cx43 (Cx32E143) in the oocyte expression system (Wang et al 2007).…”
Section: Pharmacology Of Hemichannelsmentioning
confidence: 88%
“…These interfere with GJ formation and inhibit hemichannel activity (Evans and Boitano, 2001; Leybaert et al, 2003). Because their initial characterization (Dahl, Nonner, & Werner, 1994), a series of “Gap” peptides with specificity for certain CX were developed (Abudara et al, 2014; Chaytor, Evans, & Griffith, 1997; Evans and Boitano 2001; Gomes, Srinivas, Van Driessche, Vereecke, & Himpens, 2005; Leybaert et al, 2003). A promising new report shows that Gap19, a nonapeptide derived from the cytoplasmic loop of CX43, inhibits astroglial CX43 hemichannels, while not affecting GJ channels (Abudara et al, 2014).…”
Section: Potential Therapeutic Targets In Astrocytesmentioning
confidence: 99%
“…Adenosine triphosphate disodium salt (Na 2 ATP), 2Ј(3Ј)-O-(4-benzoylbenzoyl) adenosine 5Ј-triphosphate triethylammonium salt (bzATP), ␣,␤-methylene ATP (␣,␤-Me-ATP), Brilliant Blue G (BBG), 4,4Ј-diisothiocyanatostilbene-2,2Ј-disulfonic acid disodium salt hydrate (DIDS), and the hemichannel blocker CBX (Gomes et al, 2005;Ma et al, 2009) were purchased from Sigma-Aldrich. CuCl 2 and ZnCl 2 (0.1 M stock solution) were also purchased from Sigma-Aldrich.…”
Section: Introductionmentioning
confidence: 99%